The Sharing of Risks and the Risks of Sharing: Solidarity and Social Justice in the Welfare State - Schuyt, Kees (Ethical theory and moral practice, 1998)
Solidarity as a social phenomenon means a sharing of feelings, interests, risks and responsibilities. The Western-European Welfare State can be seen as an organized system of solidarity, historically grown from group solidarity among workers, later between workers and employers, moving towards solidarity between larger social groups: between healthy people and the sick, between the young and the elderly, between the employed and the unemployed. This sharing of risks at a societal level however, has revealed the risks of sharing. In the postwar development of the welfare state, solidarity has been organized mainly in administrative forms, run by anonymous bureaucracies and giving way to free riders and calculative citizens. This article describes this development and provides arguments for a reorientation of the welfare state and for the re-allocation of rights, risks and responsibilities.